The Effect of Water Exercise Program on Static and Dynamic Balance in Elderly Women - Heydar Sadeghi; Fatemeh Alirezaei (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: Poor balance is one of risk factors of falling, a cause of injury and even death in elderly. The aim of this study was to evaluate the effect of a water exercise program on static and dynamic balance in elder women. Methods & Materials: Thirty participants aged 55-70 years completed an exercise program (60 min, 3 days and 6 weeks), in 2 groups, exercise and control, voluntarily. Static and dynamic balances were measured before and after exercise program in both groups. Postural sway parameters, including mean displacement of center of pressure and velocity of center of pressure in Medio-Lateral (ML) and Anterio-Posterior (AP) directions, in single stance position, as a measure of static balance and functional reach test, functional reach right test and functional reach left test, as dynamic measure of balance was considered. T test for deepened groups was used for evaluation of changes within groups, and T test for independent groups was used for between groups' changes at threshold of 0.05 After 6 weeks. Results: Significant changes were observed in results of Functional Reach Test (FRT), Functional Reach Left Test (FRLT) after exercise program, also in average displacement of cop and velocity of cop in ML direction. Between groups significant differences were observed in results of average cop displacement and velocity of displacement, FRT and FRLT. Conclusion: These results suggest that challenging the physiological systems involved in balance control, in water, while on the non stable support surface, improved both static and dynamic balance and probably might decrease the risk of falling.